PROFESIONALISME NABI MUHAMMAD SAW SEBAGAI PERINTIS PERTAMA LEMBAGA PAI DAN KELAYAKANNYA SEBAGAI GURU BESAR PERTAMA - Mafruhah, Mafruhah (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2018)
The Education of PAI does not stand by itself, but there is an initial process of formation. It has been told in history, among the pioneers in the establishment of the first formal education as well as the founder (founder) was the Prophet Muhammad SAW whose institution was centered in the mosque, because there was a connection with his duties as an educator (teacher). So from that the propriety of giving to the Prophet Muhammad SAW as the first professor in the field of PAI.